2007
DOI: 10.1104/pp.107.110817
|View full text |Cite
|
Sign up to set email alerts
|

ECA3, a Golgi-Localized P2A-Type ATPase, Plays a Crucial Role in Manganese Nutrition in Arabidopsis

Abstract: Calcium (Ca) and manganese (Mn) are essential nutrients required for normal plant growth and development, and transport processes play a key role in regulating their cellular levels. Arabidopsis (Arabidopsis thaliana) contains four P 2A -type ATPase genes, AtECA1 to AtECA4, which are expressed in all major organs of Arabidopsis. To elucidate the physiological role of AtECA2 and AtECA3 in Arabidopsis, several independent T-DNA insertion mutant alleles were isolated. When grown on medium lacking Mn, eca3 mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 58 publications
(80 reference statements)
5
160
2
Order By: Relevance
“…As CPA at a concentration that induced [Ca 2+ ] cyt oscillations did not completely deplete the [Ca 2+ ] ER in this study, a CPA-insensitive Ca 2+ -ATPase in the ER might be related with the [Ca 2+ ] cyt oscillations. In addition, ECA3, another IIA-type Ca 2+ -ATPase from Arabidopsis, has been detected in the Golgi apparatus (Mills et al, 2008), and a CPA-sensitive Ca 2+ pump has been identified in both ER vesicles and the Golgi apparatus of Pisum sativum (Ordenes et al, 2002). Furthermore, vesicle accumulation independent of the ER was observed in the pollen tip of L. longiflorum (Parton et al, 2003;Bove et al, 2008).…”
Section: Dynamics In Arabidopsis Pollen Tubesmentioning
confidence: 84%
“…As CPA at a concentration that induced [Ca 2+ ] cyt oscillations did not completely deplete the [Ca 2+ ] ER in this study, a CPA-insensitive Ca 2+ -ATPase in the ER might be related with the [Ca 2+ ] cyt oscillations. In addition, ECA3, another IIA-type Ca 2+ -ATPase from Arabidopsis, has been detected in the Golgi apparatus (Mills et al, 2008), and a CPA-sensitive Ca 2+ pump has been identified in both ER vesicles and the Golgi apparatus of Pisum sativum (Ordenes et al, 2002). Furthermore, vesicle accumulation independent of the ER was observed in the pollen tip of L. longiflorum (Parton et al, 2003;Bove et al, 2008).…”
Section: Dynamics In Arabidopsis Pollen Tubesmentioning
confidence: 84%
“…The P-type ATPases AtECA1 (localized at the endoplasmic reticulum) and AtECA3 (expressed in the Golgi complex) participate in the influx of Mn (Li et al, 2008;Mills et al, 2008). The cation/H exchanger (CAX) transporters AtCAX2 and AtCAX4, which were originally identified as Ca transporters, also have the ability to transport Mn into the vacuole (Connorton et al, 2012;Korenkov et al, 2007).…”
Section: Manganese Uptake By Plantsmentioning
confidence: 99%
“…In the chloroplasts of both Arabidopsis and barley, HMA1 contributes to Zn detoxification by exporting Zn from the plastids to the cytoplasm Mikkelsen et al, 2012). It has been proposed that the Golgi-localized transporter AtECA3 may have a role in the mobilization of Zn from the cytoplasm to the Golgi complex (Barabasz et al, 2011;Mills et al, 2008).…”
Section: Figmentioning
confidence: 99%
“…EF hands in K + channel-interacting proteins have been shown to be essential for correct trafficking of mammalian K + channel proteins (Flowerdew and Burgoyne, 2009). A role for Ca 2+ in the recognition and vacuolar sorting of the ER-like Ca/Mn-ATPase ECA3 and Ca 2+ -dependent recognition of cargo proteins has also been inferred (Li et al, 2008, Mills et al, 2008. Patch clamp recordings show little effect of cytoplasmic Ca 2+ on the activity of either TPKa or TPKb, indicating that the putative EF domains in these proteins may not be functional.…”
Section: The Tpk C Terminus Affects Tpk Membrane Localizationmentioning
confidence: 99%